2019
DOI: 10.1016/j.regsciurbeco.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Public transport and urban pollution

Abstract: The paper studies the effect of public transport policies on urban pollution. It uses a quantitative equilibrium model with residential choice and mode choice. Pollution comes from commuting and residential energy use. The model parameters are calibrated to replicate key variables for American metropolitan areas. In the counterfactual, I study how free public transport coupled with increasing transit speed affects the equilibrium. In the baseline simulation, total pollution falls by 0.2%, as decreasing emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 30 publications
0
17
0
2
Order By: Relevance
“…The reason is that, as analyzed by the theoretical literature, residents of densely populated cities consume less fuel due to the availability of public transport systems and shorter commutes, and use less residential energy because dwellings are smaller and high-rise apartment buildings are more energy efficient. Indeed, per capita fuel consumption and automobile utilization have been found to be significantly lower in more densely populated cities due to the availability of public transport and shorter commutes to work on average (Newman and Kenworthy, 1989;Karathodorou et al, 2010), and public transport has been found to reduce pollution (Bauernschuster et al, 2017;Borck, 2017). Gudipudi et al (2016) use U.S. data from 2000 and find that per capita CO 2 emissions decrease with city size.…”
Section: Related Literaturementioning
confidence: 99%
“…The reason is that, as analyzed by the theoretical literature, residents of densely populated cities consume less fuel due to the availability of public transport systems and shorter commutes, and use less residential energy because dwellings are smaller and high-rise apartment buildings are more energy efficient. Indeed, per capita fuel consumption and automobile utilization have been found to be significantly lower in more densely populated cities due to the availability of public transport and shorter commutes to work on average (Newman and Kenworthy, 1989;Karathodorou et al, 2010), and public transport has been found to reduce pollution (Bauernschuster et al, 2017;Borck, 2017). Gudipudi et al (2016) use U.S. data from 2000 and find that per capita CO 2 emissions decrease with city size.…”
Section: Related Literaturementioning
confidence: 99%
“…Urban air pollution comes mainly from commuting or transport, economic activities and residential energy use ( Borck, 2019 ; Grondys, 2019 ). When there are measures to control vehicular flow or industrial emissions, the levels of air pollutants are reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the quality and quantity of public transport services is one of the most efficient transport policies to improve modal split and reduce car use, with positive impacts on emissions [204][205][206][207][208][209][210][211][212][213]. Countries that invest the most in public transport systems are also those with the highest shares of modal split.…”
Section: Transit Improvements and Public Transport Promotionmentioning
confidence: 99%